Seungmagalgeun-Tang, a Traditional Herbal Formula, Alleviates Skin Inflammation and Depression-Like Behavior in Atopic Dermatitis Mice under Sleep Deprivation Conditions. (23rd March 2022) - Thi Huong Nguyen, Ly; Choi, Min-Jin; Shin, Heung-Mook; Yang, In-Jun
Abstract : Atopic dermatitis (AD) is a common inflammatory skin disease, which can be worsened under sleep deprivation (SD) conditions. This study investigated the efficacy and the mechanism of action of the traditional herbal formula Seungmagalgeun-tang (SMGGT) on the inflammation and behavioral changes in a mouse model of AD exposed to SD. SMGGT decreased levels of IgE, TNF- α, IL-4, IL-13, and mast cell infiltration and reduced the expression of CD3 in the mouse skin. SMGGT also reversed the SD-induced increase in corticosterone and decrease in melatonin level. Furthermore, SMGGT reduced the immobility time in the tail suspension test significantly. HaCaT cells and HMC-1 cells were used to investigate the effects of SMGGT on cell signaling pathways. In TNF- α /IFN- γ (TI) treated HaCaT cells, SMGGT reduced production of TARC/CCL17 and MDC/CCL22 and suppressed the p38 MAPK, STAT1, and NF- κ B pathways. In substance P (SP)/CRH-stimulated HMC-1 cells, SMGGT decreased VEGF production and inhibited ERK phosphorylation. Network pharmacology and molecular docking analysis revealed that puerarin and paeoniflorin might contribute to the effects of SMGGT by targeting several AD-related molecules and pathways. Puerarin and paeoniflorin exerted anti-inflammatory effects by decreasing production of MDC/CCL22 and IL-6 in TI-treated HaCaT cells and VEGF production in SP/CRH-stimulated HMC-1 cells. This study suggests that SMGGT with puerarin and paeoniflorin as main bioactive components alleviates skin inflammation and depression-like behavior in a sleep-deprived mouse model of AD.